Greg Woods COVID-19 World War I Propaganda - Woods, Greg::::::::: (2022)
A modified image of a World War I propaganda poster with an image of the COVID-19 virus covering the face of the "mad brute," with added captions, "CORONAVIRUS AND THE CONSTITUTIONAL IMPERATIVE," "CONTINUITY OF GOVERNMENT," "SHELTER IN PLACE," and "FORCE MAJEURE." This is one of two COVID-19 art pieces created by Greg Woods.